Pengaruh Promosi, Harga dan Kepuasan Pelanggan Terhadap Penjualan pada UMKM di Sektor Percetakan Kota Medan - Royhan Ali Hasyim Hutapea; Mustafa Kamal Rokan; Rahmat Daim Harahap (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to examine and analyze how and to what extent advertising, price and customer satisfaction affect the sales of MSMEs in the Medan printing sector. The research method used in this study is a quantitative method with a descriptive approach. The data used is primary data collected from respondents and SMEs. The target of this survey is printing in the city of Medan, and the target survey is data of 50 respondents. This study uses the SPSS 20.0 test device for classical hypothesis testing, multiple regression analysis, and hypothesis testing. Based on the results of the hypothesis test or t-test, it can be shown that: Promotion will partially have a significant positive impact on the sales of MSMEs in the printing sector in the city of Medan. Prices have a significant positive impact on the sales of MSMEs in the Medan printing sector. Customer satisfaction has a significant positive impact on MSME sales in the Medan printing sector. And the results of the F test show that the quality of advertising, price and service have a significant positive effect on the sales of MSMEs in the printing sector in Medan city. Together, the results of this test show that the variables of promotion, price, and service quality contribute 74.4% to the sales variable. Price and service quality have a significant positive effect on the sales of Medan printing MSMEs. Together, the results of this test show that the variables of promotion, price, and service quality contribute 74.4% to the sales variable. Price and service quality have a significant positive effect on the sales of Medan printing MSMEs. Together, the results of this test show that the variables of promotion, price, and service quality contribute 74.4% to the sales variable.